McGraw-Hill dictionary of bioscience - Parker, Sybil P. (McGraw-Hill, 1997)
This comprehensive reference defines nearly 16,000 essential terms in the biosciences. Biologists, researchers, technicians, educators, and students will have access to accurate definitions covering the fields of anatomy, embryology, physiology, cell biology, morphology, taxonomy, genetics, immunology, virology, evolution, and molecular biology. Valuable appendices are also included.